The Influence of Instagram Social Media and Product Diversity on Customer Purchasing Decisions at Café Anaugӧlӧ Kofi Medan - Lia Damanik; Dina Sarah Syahreza (Indonesian Journal of Economic & Management Sciences, 2023)
This research aims to explore the impact of Instagram social media and product variations on customer purchasing decisions at Anaugӧlӧ Kofi Medan. The research method used was quantitative, using accidental sampling, involving 97 respondents. Data analysis was carried out using multiple linear regression via the SPSS for Windows 24.0 program. The research results show that partially, Instagram social media and product variations have a positive and significant influence on purchasing decisions. The coefficient of determination test indicated that around 36.9% of purchasing decisions were influenced by Social Media Instagram and product variety, while other factors outside the scope of the study played a role in the remainder